125 years of legacy data at the Geological Survey of Western Australia: Capture and delivery. (June 2015) - Riganti, Angela; Farrell, Terence R.; Ellis, Margaret J.; Irimies, Felicia; Strickland, Colin D.; Martin, Sarah K.; Wallace, Darren J.
Abstract: For over a century the Geological Survey of Western Australia has been accumulating an enormous amount of information on the geology, mineral resources, and petroleum fields of Western Australia, either through the activities of State-employed regional mappers or the submission of mineral and petroleum reports mandated by State legislation. Recognizing the importance of this legacy for future exploration and research, in the last 25 years the Survey has been digitally capturing this information into custom-designed systems/databases that collate data on, amongst others, field observations (WAROX, for 'Western Australia Rocks'), mineral exploration reports (WAMEX), and petroleum exploration information (WAPIMS). Data are made available to the public through the GeoVIEW.WA web application, designed in-house to view and query these integrated geoscientific and related datasets.